NFC Based Smart Mobile Attendance System - Baykara, Muhammet; Gurturk, Ugur; Karakaya, Ertugrul (Ieee, 2017)
In today's rapidly evolving world of information and technology, software that tries to respond to growing demands is used in many industries. Everything can be made easier and faster with mobile platforms and smart PCs that almost everyone now has. Different types of technology can be managed and used, in various area such as shopping, banking, education. In this study, a mobile software was developed which enables to report the signature system that applied in educational institutions as a digital system with minimum error rate. Thanks to the intelligent attendance system developed using NFC technology, NFC tags of users can be used to track their participation according to their location and time of interaction successfully.
NFC Tabanh Akilli Mobil Yoklama Sistemi
2017 International Conference on Computer Science and Engineering (UBMK) -- OCT 05-08, 2017 -- Antalya, TURKEY
Keywords: mobile programming; smart attendance system; NFC technology; mobile attendance system; location based services